Anh văn chuyên ngành (xây dựng) - MSc. Võ Minh Huy (Trường Đại học Trà Vinh, 2020)
Unit 1: History of architecture. Unit 2: Housing in Britain. Unit 3: The procedure of building construction. Unit 4: Design of houses for tropical climates. Unit 5: Structures. Unit 6: Foudations. Unit 7: Building materials. Unit 8: Site labour. Unit 9: Planning design process. Unit 10: Current environmental situation.